Los estados financieros para la toma de decisiones: caso de estudio escuela de conducción Rodar del cantón Machala. - Cuenca Ajila, Narcisa Del Carmen (2017)
The interpretation and the financial analysis is an extremely important aspect for the organizations, because its correct analysis allows to know about the economic facts happened in the past and in this way to predict the future in relation to the diverse economic activities that are realized. The city of Machala, characterized by being a pole of development in the south of Ecuador, is settled innumerable companies that seek to somehow fulfill their financial objectives as management. Among the companies mentioned are the driving schools, the same that from the approval of new Land Transport, Transit and Security Law in July 2008 operate under the authorization National Commission for Land Transport, Traffic and Road Safety, by means of the present analysis will be exposed the problematic found, of the companies, because they can know with precision the situation of the operations realized in the organizations and in this way obtain firm basis to give an opinion. The present work will be carried out in the non-professional driving school of the city of Machala, Rodar, in this way that the population to analyze also comprises those people who are part of the financial area of these organizations. An information collection instrument will be used in the area of accounting, which will determine the importance of the importance of the financial analysis. The general objective of the present investigation is: To determine in what way the uncertainty of the Financial Statements affects in the management decision making in the driving school of the canton Machala. The methodology applied in the present research work allowed the present work to be carried out under a quantitative and qualitative approach to determine the importance of the analysis of the financial statements for decision making in the rolling and quantitative driving school because the data should be examined numerically, directed to the results. This project was based on documentary and field research. In the Rodar driving school in the city of Machala, based on the survey, a compliance with the organizational objectives is evidenced, organizational objectives give managers and other members of the organization important parameters for action in the different areas of the company. The survey of the organization's staff also showed that there is concern about knowing the actual financial situation of the organization, which allows it to take the appropriate measures to ensure its normal operation and to keep growing. With respect to financial ratios, these show that although their profitability rates are not very high, those that can be the result of competition in the market, they have been able to remain constant which gives the company some stability. It is also important to mention that it has a high liquidity index with those that, if necessary, can fulfill its commitments.